(untitled) (Ius Novum, 2020)
The author of this gloss accepts the argument that the existence of ‘exceptionally justified circumstances’ within the meaning of Article 60 § 2 CC should be inferred from unusual circumstances of the incident or the features of the perpetrator which characterise them in an exceptionally positive way and warrant the imposition of a penalty lesser than the least severe penalty imposable for the offence in question. Based on a review of court decisions and scholarly works, the author identifies the key determinants guiding the assessment of whether exceptionally justified circumstances exist. Furthermore, the author endorses the call for maintaining an appropriate standard of appellate review in cases involving the extraordinary mitigation of a penalty. Such a standard implies the need for a substantive and not merely formal revision of the grounds for the appeal challenging the legitimacy of the application of the extraordinary mitigation of a penalty.